Zircon U–Pb ages of Lohit Plutonic Complex, NE India: Constraints on episodic magmatism of eastern Trans‐Himalaya. Issue 2 (23rd December 2021) - Pebam, James; Duraisamy, Kamalakannan; Krishna, Kalyanam V.S.S.; Sengupta, Siladitya; Ghosh, Joy Gopal; Kumar, Rajeev; Basak, Krishnapriya; Guha, Dipayan
Abstract : The Lohit Plutonic Complex (LPC) represents Trans‐Himalayan magmatic rocks in the easternmost sector of the Himalayan Orogen. It is divided into leucogranite‐granodiorite‐diorite dominant suite in the NE and the gabbro‐diorite‐granodiorite‐granite–trondhjemite suite in the SE by the Walong Thrust. U–Pb geochronological analyses of euhedral zircon grains from different magmatic phases of LPC reveal episodic magmatism. Zircon U–Pb age of 153.4 ± 1.4 Ma of a garnetiferous granite gneiss suggest that the crustal sourced magmatism was active in Arunachal Trans‐Himalaya during the late Jurassic. U–Pb ages of subduction induced magmatic rocks of LPC range between 117 ± 0.6 Ma and 49.5 ± 0.3 Ma. A significant contribution in crustal recycling during the Oligocene–Miocene is evident from crustally derived leucogranites having U–Pb ages ranging from 35.6 ± 0.3 Ma to 30 ± 0.3 Ma. A comparison of the crystallization ages of the Western Trans‐Himalayan units with those of eastern Trans‐Himalayan units reveals an earlier onset of Tethyan arc magmatism in the eastern sector. The most prominent phase in the eastern sector is during the Late Cretaceous while western and central sector show major activity during the Palaeocene–Eocene. Abstract : Zircon U–Pb ages of subduction induced magmatic rocks of Lohit Plutonic Complex range between 117 ± 0.6 Ma and 49.5 ± 0.3 Ma. A significant crustal recycling during Oligocene–Miocene is evident from crustally derived leucogranites having U–Pb ages ranging from 35.6 ± 0.3 Ma to 30 ± 0.3 Ma. The most prominent magmatic phase in the eastern Trans‐Himalayas is during Late Cretaceous while western and central sector show major activity during Palaeocene–Eocene.